Patient and professional experiences of palliative care referral discussions from cancer services: A qualitative interview study. (13th October 2020) - Pini, Simon; Hackett, Julia; Taylor, Sally; Bekker, Hilary L.; Kite, Suzanne; Bennett, Michael I.; Ziegler, Lucy
Abstract: Objectives: The aim of this paper was to identify current barriers, facilitators and experiences of raising and discussing palliative care with people with advanced cancer. Methods: Semi‐structured interviews were conducted with patients with advanced cancer and healthcare professionals (HCPs). Patients were included who had and had not been referred to palliative care. Transcripts were analysed using framework analysis. Results: Twenty‐four patients and eight HCPs participated. Two overarching themes and five sub‐themes emerged: Theme one—referral process: timing and triggers, responsibility. Theme two—engagement: perception of treatment, prognosis and palliative care, psychological and emotional preparedness for discussion, and understanding how palliative care could benefit present and future care. Conclusion: There is a need to identify suitable patients earlier in their cancer trajectory, address misconceptions about palliative care, treatment and prognosis, and better prepare patients and HCPs to have meaningful conversations about palliative care. Patients and HCPs need to establish and communicate the relevance of palliative care to the patient's current and future care, and be clear about the referral process.